2018
DOI: 10.1097/md.0000000000011376
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in systemic lupus erythematosus

Abstract: Depression and anxiety cause severe loss of quality of life for patients with systemic lupus erythematosus. The causes and factors that contribute to these psychological manifestations in lupus are difficult to disentangle. This study compared clinical, psychological, and demographic factors between lupus patients, depressed patients, and rheumatoid arthritis patients to discover lupus-specific contributors to depression. Lupus-specific manifestations of depression were also investigated.Physiological, clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 59 publications
3
46
1
10
Order By: Relevance
“…This study found no significant relationship between age with anxiety and depression and therefore supports the findings by previous studies carried out in other countries (Bachen, Chesney & Criswell, 2009;Beckerman, Auerbach & Blanco, 2011;Nery, Borba, Hatch, Soares, & Neto, 2007;Stoll et al 2001;Figueredo-Braga et al 2016). However, Mak and friends found a significant relationship between age with both of anxiety and depression in Singapore (Mak et al 2011).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study found no significant relationship between age with anxiety and depression and therefore supports the findings by previous studies carried out in other countries (Bachen, Chesney & Criswell, 2009;Beckerman, Auerbach & Blanco, 2011;Nery, Borba, Hatch, Soares, & Neto, 2007;Stoll et al 2001;Figueredo-Braga et al 2016). However, Mak and friends found a significant relationship between age with both of anxiety and depression in Singapore (Mak et al 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Because developments in treatment of diseases were currently growing rapidly in University Kebangsaan Malaysia Medical Centre (UKMMC), many patients regardless of rural or urban areas were referred to UKMMC (Kong, 2009). This finding is parallel with Figueredo-Braga, Cornaby, Cortez, Bernardes, Terroso, Figueredo, Mesquita, Costa, & Poole (2016) that found 40% of patients had high level of depression and 47% of patients had high level of anxiety. Comparing the prevalence of anxiety and depression based on this study with findings by Chin and friends (1993), who studied a sample of 79 SLE patients in UKMMC, draws mixed results i.e.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The disease itself, unexpected exacerbations, medical regimen side effects, and medical care issues are often identified as the sources of depressed feelings. In addition, the question regarding which disease manifestations create the most emotional distress also remains open: there are mixed results regarding the association between lupus disease activity and depression and anxiety, with some studies showing a connection and others finding no association (Rosa Beltrão et al ., ; Figueiredo‐Braga et al ., ).…”
Section: Discussionmentioning
confidence: 97%